(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
This paper focuses on the beginning of the archaeological mission of the University of Milan at Gortys, when in 2002 the author was at the head of a new archaelogical research on the acropolis in Gortys. Since 2003 a great Roman bath building has been brought to light south of “Pretorio” within annual excavations. Al the end the paper offers some fresh thoughts on the long‐term archaeological relationship between Milan and Gortys (and vice versa), seen in the context of Serafino Ricci’s studies about Pretorio and Odeion in Gortys at the end of 19th century. Following are observations on Hygieia’s image in glyptic and eburnea diptycha.